Demographic Study of Varicella Zoster Virus in Cerebrospinal Fluid ofStroke Patients in Thi-Qar Province - Fahail, Zeena; Bushra Jabbar Hamad (University of Thi-Qar Journal of Science, 2024)
Varicella Zoster Virus (VZV), also known as alpha herpesvirus Virus 3, belongs to the Alpha Herpesviridae family and is a unique virus that can reactivate neurons and root ganglia in the nervous system and causes many neurological diseases, especially stroke. Molecular and genetic studies of viruses are valuable tools for virus development and identifying viral treatments to combat the disease. The study aims to demonstrate the causal roles of Varicella-zoster virus in the progression of stroke by detecting the presence of virus DNA in the patients CSF by real-time PCR technique. The study aimed to identify the relationship between VZV infection and demographic characteristics. The current study involved 120 participants collected in Al-Husein Teaching Hospital, of which 90 patients with systemic manifestations of the central nervous system (CNS) with/without rash and 30 participants as a control group, the age of population ranging from 1 to70 years among them 73 males and 47 females VZV DNA was detected using Quantitative real-time PCR (ORF4) from CSF. The results recorded 47 (39.17%) of both patients and control groups were positive for VZV, among them 34 (37.78%) in patients group and 13 (43.33%) cases in the control group. According to sex of patients, the females have the highest infection percentage. Also, noted that 52.78% of infection in the female group and 47.22% in the male group, regarding age groups, the sixth age group it was scored the high percentage of infection 66.67%, while the first age group scored a low infection percentage .